Reinforced and toughened Ti-6Al-4V alloy based on direct-current pulse and preparation method of reinforced and toughened Ti-6Al-4V alloy
By performing DC pulse treatment on commercial hot-processed Ti-6Al-4V alloy, the problems of poor plastic toughness and poor processing quality in room temperature plastic processing are solved, and the high strength, high toughness and low energy consumption preparation of the alloy are achieved.
Patent Information
- Application Number
- CN202411757266.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art has problems such as poor plastic toughness, severe residual stress, and poor processing quality when plastic processing of titanium alloys at room temperature, and the electrically assisted preparation process cycle is cumbersome, high cost and large energy consumption.
The enhanced toughened Ti-6Al-4V alloy preparation method based on DC electric pulse is adopted. After mechanical grinding, ultrasonic cleaning and constant temperature drying of commercial hot-processed Ti-6Al-4V alloy tensile samples, the DC electric pulse processing is performed using the ISB-300A inverter welding power supply to control the current density and electrical pulse time to optimize the mechanical properties of the alloy.
The yield strength, tensile strength, elongation, hardness and elastic modulus of Ti-6Al-4V alloy have been significantly improved, the alloy preparation cycle and energy consumption have been shortened, the process flow has been simplified, and the production cost has been reduced.
Smart Images

Figure CN119615037A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy reinforcement, and in particular relates to a direct current pulse-based reinforced and toughened Ti-6Al-4V alloy and a preparation method thereof. Background Art
[0002] Ti-6Al-4V (TC4) dual-phase titanium alloy has the characteristics of light weight, high strength and excellent corrosion resistance. It has been the focus of research in extreme technical fields such as aerospace, deep space exploration, national defense and military industry, high-voltage power transmission, and marine transportation, and has far-reaching development prospects and strategic significance. At present, difficult-to-deform metal materials represented by titanium alloys still have objective problems such as poor plastic toughness, severe residual stress, and unsatisfactory processing quality during room temperature plastic processing. Therefore, relevant workers have tried to explore the combination of mechanical alloying or heat treatment processes to solve the above problems. However, the alloying element cost of the above process is high, the heat treatment process is relatively complicated, the performance is unstable, and the production cycle is long. Therefore, it is very urgent to design a high-efficiency and low-energy titanium alloy performance optimization technology.
[0003] At present, the technology of power-assisted forming or deformation has been put into practical application in a variety of metal material systems, and has achieved the regulation of microstructure and optimization of performance to a certain extent. For example, patent CN202011050214.1 adopts an electric pulse-assisted hot stamping forming method, which fully utilizes the advantages of electro-induced stress relaxation caused by pulse current, and prepares hot stamped titanium alloy parts with small springback phenomenon and excellent comprehensive mechanical properties, which provides inspiration for solving the contradiction between part dimensional accuracy and mechanical properties. Patent CN102896193B adopts a hot spinning preparation technology assisted by an external current, that is, the Joule heat generated by the current passing through the tube blank is used to continuously heat the tube, and then combined with a certain pressure generated by the pressurizing device, the spinning forming efficiency is effectively improved. In addition, patent CN118789154A also proposes an electric pulse repair process, which heals defects such as cracks and holes inside the Ti-6Al-4V alloy to a certain extent by adjusting the pulse voltage of electric pulse heating.
[0004] Although the mechanical properties of Ti-6Al-4V alloy have been optimized to varying degrees through the above-mentioned related power-on processes, the above-mentioned electrical auxiliary equipment is complicated in design and the forming effect is heavily dependent on the equipment. Or the process control parameters of the pulse current are numerous and difficult to achieve precise control. Or the power-on period is long and the temperature is high, resulting in high energy consumption of equipment and raw materials. Therefore, the electrical treatment process cycle still needs to be further shortened, the electrical pulse treatment process needs to be simplified, the product preparation cost needs to be reduced, and the utilization efficiency of materials needs to be improved. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the strength and toughness of Ti-6Al-4V alloy materials are still not enough to be put into actual production application on a large scale and in high quantities. The traditional thermal-mechanical treatment technology and the existing electrically assisted preparation technology still have problems such as cumbersome cycle, complex process, unstable performance, high preparation cost, and unsatisfactory mechanical properties. The purpose of the present invention is to provide a reinforced and toughened Ti-6Al-4V alloy based on direct current pulses and a preparation method thereof.
[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows, comprising the following steps:
[0007] Step S1: First, wire cutting is performed on the Ti-6Al-4V alloy raw material to obtain a plurality of tensile specimens;
[0008] Among them, the Ti-6Al-4V alloy raw material uses commercial hot-processed Ti-6Al-4V alloy round bars, and the geometric dimensions of the Ti-6Al-4V alloy round bars are 30mm in diameter and 200mm in length. Subsequently, wire cutting is performed along the axial length direction of the alloy round bar to obtain multiple tensile specimens. The dimensions of the tensile specimen gauge position are 8mm in length, 2mm in width, and 1mm in thickness;
[0009] Step S2, mechanically grinding, ultrasonically cleaning and constant temperature drying the tensile specimen obtained in step S1 in sequence to obtain an initial alloy sample for direct current pulse treatment;
[0010] Step S3, then placing the initial alloy sample of step S2 on the test bench, and connecting two ends of the initial alloy sample to two copper plate electrodes in the power supply system respectively;
[0011] The power source adopts ISB-300A inverter welding power source, and the current density and direct current pulse processing time are controlled by an external numerical control panel on the power source.
[0012] Step S4, starting the power supply, subjecting the initial alloy sample to direct current pulse treatment, and subjecting the initial alloy sample after direct current pulse treatment to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence, to finally obtain a reinforced and toughened Ti-6Al-4V alloy.
[0013] The yield strength, tensile strength and elongation of the reinforced and toughened Ti-6Al-4V alloy can be tested by a tensile testing machine, and the hardness and elastic modulus of the reinforced and toughened Ti-6Al-4V alloy can be tested by a nanoindentation tester.
[0014] In the step S3, a conductive copper block is arranged between the copper plate electrode and the end of the initial alloy sample, and the conductive copper block is used to conduct electricity to the initial alloy sample.
[0015] In step S4, the specific method of performing direct current pulse treatment on the initial alloy sample is: starting the power supply and inputting an instantaneous direct current pulse of a specific current density into the initial alloy sample.
[0016] In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 ~160A / mm 2 .
[0017] In the step S4, the DC pulse processing time of the instantaneous DC pulse is 40 ms to 90 ms.
[0018] In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 , the DC pulse processing time of the instantaneous DC pulse is 75ms.
[0019] In the step S1, the chemical composition of the Ti-6Al-4V alloy raw material mainly includes: Ti, Al, V, Fe, C, and N; the mass percentage content of the aluminum Al element is 5.5% to 6.8%, the mass percentage content of the vanadium V element is 3.5% to 4.5%, the mass percentage content of the iron Fe element is 0.3% to 0.4%, the mass percentage content of the carbon C element is 0.1% to 0.2%, and the mass percentage content of the nitrogen N element is 0.05% to 0.1%.
[0020] The reinforced and toughened Ti-6Al-4V alloy of the present invention is prepared by adopting the above-mentioned preparation method.
[0021] The present invention uses instantaneous direct current pulses, and the principle is significantly different from that of electric pulses with long power-on periods. The present invention transforms the micron-sized β particles rich in V elements located in the intergranular position in the initial structure into nano-sized β phase layers located in the crystal, thereby achieving an enhanced effect. At the same time, a certain number of c+a dislocations are activated inside the α' martensite laths generated by the phase transformation of the electric pulse process, thereby improving the elongation of the titanium alloy. At the same time, a small amount of tensile twins can be observed in the electric pulse treated samples.
[0022] The present invention intends to use direct current pulse equipment to perform electric pulse treatment on hot-processed Ti-6Al-4V alloy tensile specimens. Through the thermal and non-thermal effects contained in the transient process, a series of parameters such as current density and electric pulse action duration are explored. Without the premise of complex processes such as thermal-mechanical treatment, the efficient and short-process preparation of high-strength and high-toughness Ti-6Al-4V alloy is achieved. Therefore, by applying direct current pulse treatment technology to optimize the comprehensive mechanical properties of commercial hot-processed Ti-6Al-4V alloy, the alloy preparation cycle and energy consumption are significantly shortened, which has strong practical significance and application prospects.
[0023] The beneficial effects of the present invention are:
[0024] 1. The present invention performs direct current pulse treatment on commercial hot-processed Ti-6Al-4V alloy. Under the action of instantaneous direct current pulse, the yield strength, tensile strength, elongation, hardness and elastic modulus of Ti-6Al-4V tensile samples can be effectively improved.
[0025] 2. Through the efficient direct current pulse processing method provided by the present invention, the power-on cycle is extremely short at the level of several microseconds, and the operation is simple and convenient, which synergistically achieves a significant improvement in the yield strength, tensile strength and elongation of the Ti-6Al-4V alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Comparative Example 1, engineering stress-engineering strain curves of commercial hot-processed Ti-6Al-4V alloys after direct current pulse treatment for 0-75ms in Examples 1-3;
[0027] Figure 2 Comparative Example 1, engineering stress-engineering strain curves of commercial hot-processed Ti-6Al-4V alloys after direct current pulse treatment for 75-90 ms in Examples 3-6;
[0028] Figure 3 The displacement-load curves of nanoindentation of the initial state sample of comparative example 1 and the peak performance sample of example 3.
[0029] Figure 4 For comparative example 1, the DC pulse current density of commercial hot-processed Ti-6Al-4V alloy in Examples 7-8 is 140A / mm 2 , 150A / mm 2 and 160A / mm 2 Engineering stress-engineering strain curve. DETAILED DESCRIPTION
[0030] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1: DC pulse action time 40ms
[0032] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0033] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0034] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0035] (4) A conductive copper block material is placed at the gap between the tensile test piece and the power copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0036] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm 2 ;
[0037] (6) The electric pulse treatment time is set to 40 ms (hereinafter referred to as 40 ms sample), and the DC power supply is turned on. After the DC pulse treatment is completed, the sample is removed from the fixture when the sample is completely cooled to room temperature.
[0038] (7) The samples were subjected to mechanical grinding, ultrasonic cleaning, and constant temperature drying in sequence to remove the surface oxide layer and impurities of the tensile specimens to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 40 ms samples were then repeatedly tested using a tensile testing machine.
[0039] Example 2: DC pulse action time 65ms
[0040] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0041] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0042] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0043] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0044] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm 2 ;
[0045] (6) Set the duration of the electric pulse treatment to 65 ms (hereinafter referred to as the 65 ms sample) and turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0046] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 65ms sample were then repeatedly tested using a tensile testing machine.
[0047] Example 3: DC pulse action time 75ms
[0048] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0049] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0050] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0051] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0052] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm 2 ;
[0053] (6) Set the duration of the electric pulse treatment to 75 ms (hereinafter referred to as the 75 ms sample) and turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0054] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 75ms sample were then repeatedly tested using a tensile testing machine.
[0055] Example 4: DC pulse action time 80ms
[0056] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0057] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0058] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0059] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0060] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm 2 ;
[0061] (6) Set the duration of the electric pulse treatment to 80 ms (hereinafter referred to as 80 ms sample) and turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0062] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 80ms sample were then repeatedly tested using a tensile testing machine.
[0063] Example 5: DC pulse action time 85ms
[0064] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0065] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0066] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0067] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0068] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm 2 ;
[0069] (6) Set the duration of the electric pulse treatment to 85 ms (hereinafter referred to as the 85 ms sample) and turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0070] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 85ms sample were then repeatedly tested using a tensile testing machine.
[0071] Example 6: DC pulse action time 90ms
[0072] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0073] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0074] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0075] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0076] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 280A to ensure that the average current density at the gauge position of the tensile specimen is 140A / mm2 ;
[0077] (6) Set the duration of the electric pulse treatment to 90 ms (hereinafter referred to as the 90 ms sample) and turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0078] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy. The mechanical properties of the 90ms sample were then repeatedly tested using a tensile testing machine.
[0079] Example 7: Current density is 150A / mm 2
[0080] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0081] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0082] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0083] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0084] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 300A to ensure that the current density at the gauge position of the tensile piece is 150A / mm 2 ;
[0085] (6) Set the duration of the electric pulse treatment to 75 ms (hereinafter referred to as 75 ms-150 A / mm 2 After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0086] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy, which was then repeatedly tested using a tensile testing machine at 75ms-150A / mm 2 Mechanical properties of samples.
[0087] Example 8: Current density is 160A / mm 2
[0088] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0089] (2) subjecting the tensile test piece obtained in step (1) to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain raw materials for mechanical testing of the initial state sample;
[0090] (3) Subsequently, a direct current pulse device is used to process the tensile specimen having a smooth surface and no defects after being processed in step (2) and placed on a specimen fixture external to the welding power supply device;
[0091] (4) A conductive copper block material is placed at the gap between the tensile specimen and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0092] (5) After the tensile specimen is installed, set the input current of the inverter welding power supply to 320A to ensure that the current density at the gauge position of the tensile piece is 160A / mm 2 ;
[0093] (6) Set the duration of the electric pulse treatment to 75 ms (hereinafter referred to as 75 ms-160 A / mm 2 After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture.
[0094] (7) Mechanical grinding, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the tensile specimen to obtain a reinforced and toughened Ti-6Al-4V alloy, which was then repeatedly tested using a tensile testing machine at 75ms-160A / mm 2 Mechanical properties of samples.
[0095] Comparative Example 1
[0096] The commercial hot-processed Ti-6Al-4V alloy was selected as the initial material, and its mechanical properties were directly analyzed:
[0097] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with a diameter of 30 mm and a length of 200 mm were wire cut to obtain multiple sets of tensile specimens. The length, width and thickness of the tensile specimens at the gauge position were 8 mm, 2 mm and 1 mm, respectively;
[0098] (2) The tensile test piece obtained in step (1) is subjected to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence to obtain the raw material for mechanical testing of the initial state sample, and the initial yield strength, tensile strength and elongation are directly tested using a tensile testing machine. The initial state sample is set as the reference group and is not subjected to any DC pulse treatment;
[0099] (3) Repeat the test of the mechanical properties of the initial tensile specimen for at least three times to ensure the reliability of the performance.
[0100] The tensile deformation test was carried out on the Ti-6Al-4V alloy samples treated with direct current pulses in Examples 1-3 and the initial state sample in Comparative Example 1 at room temperature, and the strain rate was selected as 10 -3 / s, equipped with a video extensometer to calculate strain in real time, the engineering stress-strain curve results are as follows Figure 1 The tensile deformation test was carried out at room temperature on the Ti-6Al-4V alloy samples treated with direct current pulses in Examples 3-6 and the initial state sample in Comparative Example 1. The tensile strain rate was 10 -3 / s, equipped with a video extensometer to calculate strain in real time, the engineering stress-strain curve results are as follows Figure 2 As shown. 75ms-140A / mm for the best combination of strength and toughness 2 The electric pulse sample and the initial state sample were subjected to nanoindentation test analysis respectively, and the load-displacement curve results of the indenter extrusion process are shown in the figure. Figure 3 shown.
[0101] Figure 1 The engineering stress-strain curves of the Ti-6Al-4V alloy samples treated with direct current pulses in Examples 1-3 and the initial state sample in Comparative Example 1 are shown in FIG. Figure 1It can be seen that without direct current pulse treatment (0ms), when the sample undergoes the elastic deformation stage, the strain hardening phenomenon of the initial sample is not obvious. At this time, the yield strength of the initial sample is 871.3MPa, the tensile strength is 947.6MPa, and the elongation is 13.5%. When the direct current pulse treatment time is 40ms, the strain hardening phenomenon of the 40ms sample is slightly enhanced, and the yield strength and tensile strength are slightly increased to 881.6MPa and 968.3MPa, respectively, but the elongation is slightly reduced to 12.2%. When the electric pulse duration is further increased to 65ms, when the plastic deformation process of the sample shows continuous strain hardening behavior, the tensile strength (1060.9MPa) and elongation (15.8%) are simultaneously improved, but its yield strength (860.4MPa) is slightly lower than that of the 40ms sample. When the electric pulse duration is 75ms, the yield strength and tensile strength of the Ti-6Al-4V alloy sample are significantly increased to 1066.0MPa and 1215.4MPa, and the elongation is 15.5%, which is 14.8% higher than that of the initial sample. It can be inferred that when the current density is 140A / mm 2 When the DC pulse treatment time was 75ms, the yield strength, tensile strength and elongation of the Ti-6Al-4V alloy were significantly optimized at the same time.
[0102] Figure 2 The engineering stress-strain curves of the Ti-6Al-4V alloy samples treated with direct current pulses in Examples 3-6 and the initial state samples in Comparative Example 1. When the direct current pulse time increases to 80ms, the yield strength, tensile strength and elongation of the Ti-6Al-4V alloy are simultaneously reduced to 1048.0MPa, 1141.5MPa and 14.3%. When the direct current pulse time is further increased to 85ms, the Ti-6Al-4V alloy becomes obviously embrittled, and the yield strength, tensile strength and elongation are 1105.1MPa, 1223.9MPa and 10.2% respectively. When the electric pulse treatment time is selected to be 90ms, the elongation of the Ti-6Al-4V alloy is only 3.9%. In summary, it can be inferred that when the direct current pulse treatment time is too long, the Ti-6Al-4V alloy gradually becomes embrittled, and both the strength and toughness are significantly reduced.
[0103] Figure 3The displacement-load curves of the nanoindentation of the DC pulse (75ms) sample and the initial state sample in Example 3. This study uses a KLA G200X nanoindenter equipped with a Berkovich diamond indenter. The depth of the indenter pressing into the sample surface is uniformly set to 1000nm, and the minimum spacing between two adjacent indentations is set to 80μm to avoid interference from test errors and obtain reliable test values. When the indenter penetration depth reaches 1000nm, the loads required for the two samples are 72.0mN and 94.8mN, respectively. It means that at the same penetration depth, the DC pulse (75ms) sample requires a higher load, and its average hardness and elastic modulus are 4.7GPa and 128.3GPa, respectively, which are 38.2% and 13.3% higher than the hardness (3.4GPa) and elastic modulus (113.2GPa) of the initial state sample, respectively.
[0104] Figure 4 For Example 7-8, the DC pulse treatment is 75ms-140A / mm 2 ,75ms-150A / mm 2 and 75ms-160A / mm 2 When the electric pulse duration is set to 75ms, the current density of Ti-6Al-4V alloy is increased from 140A / mm 2 Increased to 150A / mm 2 and 160A / mm 2 When the current density is increased, the yield strength and tensile strength of the Ti-6Al-4V alloy are almost unchanged, and the elongation is reduced to 14.2% and 10.0%, respectively. The results show that further increasing the current density will significantly reduce the plasticity and toughness of the Ti-6Al-4V alloy.
[0105] The yield strength, tensile strength and elongation of the initial Ti-6Al-4V alloy sample prepared in Comparative Example 1 and the DC pulse samples obtained in Examples 1-6 were compared at room temperature. The results are shown in Table 1.
[0106] Table 1 Summary of mechanical properties at different electric pulse treatment times
[0107]
[0108]
[0109] The yield strength, tensile strength and elongation of the initial Ti-6Al-4V alloy sample prepared in Comparative Example 1 and the DC pulse samples obtained in Examples 7-8 were compared at room temperature. The results are shown in Table 2.
[0110] Table 2 Summary of mechanical properties at different electric pulse current densities
[0111]
[0112] It can be seen from Table 1 that when the current density is kept constant, as the DC pulse duration continues to increase, the tensile strength and elongation of the DC pulse Ti-6Al-4V alloy samples obtained in Examples 1-6 both show a trend of first increasing and then decreasing. 2 When the treatment time is 75ms, the strength and toughness of Ti-6Al-4V alloy are significantly improved compared with the initial state. At this time, the yield strength, tensile strength and elongation are 1066.0MPa, 1215.4MPa and 15.5% respectively. It can be seen from Table 2 that when the DC pulse duration is kept constant, as the current density continues to increase, the electric pulse still maintains a continuous strengthening effect on the Ti-6Al-4V alloy, but the toughness continues to decrease.
[0113] It can be seen from the above examples and comparative examples that the yield strength, tensile strength and elongation of the commercial hot-processed Ti-6Al-4V alloy treated by direct current pulse treatment provided by the present invention are significantly improved at the same time. Current density 140A / mm 2 The average values of hardness and elastic modulus of the sample with electric pulse time of 75ms increased by 38.2% and 13.3% respectively compared with the initial state.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse, characterized in that: The following steps are involved: Step S1, first, wire cutting is performed on the Ti-6Al-4V alloy raw material to obtain a plurality of tensile specimens; Step S2, mechanically grinding, ultrasonically cleaning and constant temperature drying the tensile specimen obtained in step S1 in sequence to obtain an initial alloy sample for direct current pulse treatment; Step S3, then placing the initial alloy sample of step S2 on the test bench, and connecting two ends of the initial alloy sample to two copper plate electrodes in the power supply system respectively; Step S4, starting the power supply, subjecting the initial alloy sample to direct current pulse treatment, and subjecting the initial alloy sample after direct current pulse treatment to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence, to finally obtain a reinforced and toughened Ti-6Al-4V alloy.
2. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In the step S3, a conductive copper block is arranged between the copper plate electrode and the end of the initial alloy sample, and the conductive copper block is used to conduct electricity to the initial alloy sample.
3. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In step S4, the specific method of performing direct current pulse treatment on the initial alloy sample is: starting the power supply and inputting an instantaneous direct current pulse of a specific current density into the initial alloy sample.
4. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 ~160A / mm 2 .
5. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In the step S4, the DC pulse processing time of the instantaneous DC pulse is 40 ms to 90 ms.
6. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 , the DC pulse processing time of the instantaneous DC pulse is 75ms.
7. The method for preparing a reinforced and toughened Ti-6Al-4V alloy based on direct current pulse according to claim 1, characterized in that: In the step S1, the chemical composition of the Ti-6Al-4V alloy raw material mainly includes: Ti, Al, V, Fe, C, and N; the mass percentage content of the aluminum Al element is 5.5% to 6.8%, the mass percentage content of the vanadium V element is 3.5% to 4.5%, the mass percentage content of the iron Fe element is 0.3% to 0.4%, the mass percentage content of the carbon C element is 0.1% to 0.2%, and the mass percentage content of the nitrogen N element is 0.05% to 0.1%.
8. A reinforced and toughened Ti-6Al-4V alloy based on direct current pulse, characterized in that: The reinforced and toughened Ti-6Al-4V alloy is prepared by the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Current-assist hot spinning forming method for titanium and titanium alloy
CN102896193B
A method and apparatus for electro-pulse assisted hot stamping forming of titanium or titanium alloy
CN112246944B
Photoelectric pulse composite processing method of novel composite microstructure of Ti-6Al-4V alloy
CN105177479A
Titanium alloy strong toughening treatment method based on pulse current
CN110592509A
Strengthening and toughening method of non-ferrous metal material
CN111575612A